The Preventive Role of Perceived Social Support in Postpartum Psychiatric Morbidity: Insights from a Rural Tertiary Care Teaching Hospital in South India - Keya Das; Sumalatha Ryali; Ritu Varma Jampana; S. Ashwini (Indian Journal of Social Psychiatry, 2025)
Introduction: Postpartum psychiatric disorders show a rising trend in developing countries, where the lack of social support is a major risk factor. Evidence from Western scientific literature also reports of similar preventive role of social support in postpartum psychiatric states. However, the attitudes toward childbearing may differ across cultures and also within the same cultural sphere. With this background, we aimed to assess the perceived social support and its association with postpartum psychiatric morbidity in a rural setting in South India. Methodology: A total of 100 postpartum women who met the inclusion and exclusion criteria were included in the study following their consent. Sociodemographic data sheet and Edinburgh Postnatal Depression Scale, Diagnostic and Statistical Manual of Mental Disorders, fourth edition, Text Revision (DSM IV-TR), and Multidimensional Scale of Perceived Social Support were administered on them. Appropriate statistical analysis was done. P <0.05 was considered statistically significant. Results: The majority of our sample recorded high perceived social support (76%), with 90% reporting high support from a special person. 10% had major depressive disorder, out of which 6% recorded melancholia, and 7% recorded suicidality on DSM IV-TR. Increasing age had lower perceived social support, P = 0.024. As perceived social support was reduced, increased psychiatric morbidity was significantly noted, with suicidality and melancholia. Conclusions: Our study finds a significant association between perceived social support and postpartum depression (PPD). Lesser social support was associated with increased suicidality and melancholia features in cases of PPD. Amplification of social support in expectant mothers is a useful way to safeguard against postpartum psychiatric disorders.